Work Engagement Ditinjau dari Psychological Well-being pada Karyawan PT. Sumatera Berlian Motors - Angel Paramitta; Achmad Irvan Dwi Putra; Sarinah Sarinah (Faculty of Psychology, Universitas Semarang, 2020)
Due to fierce competition between organizations, the relevant organizations need to develop every resource they have, especially Human Resources. Good employee performance may improve the quality of organization. This happens through vigor, dedication and absorption in work, which is called engagement. To improve this, employees need to feel happy and comfortable with their work. This study aims to determine relationship between psychological well-being and work engagement. The subjects in this study were 114 employees of PT. Sumatera Berlian Motors selected with the purposive sampling method. The results of data analysis with the Pearson Product Moment showed coefficient of r = 0.315 and a significance value of 0,000 (p <0.05). This shows that there is positive relationship between psychological well-being and work engagement. Based on the results of this study, it can be concluded that the research hypothesis is accepted, namely there is positive relationship between psychological well-being and work engagement.